2023
DOI: 10.4103/ijo.ijo_1766_22
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge among paramedical staff about glaucoma surgeries and post-surgery counseling – A questionnaire based study at a tertiary eye care center in Central Rural India

Abstract: Purpose: To determine the level of awareness and knowledge about glaucoma surgery and post-surgery counseling amongst paramedical staff at a tertiary eye-care hospital. Methods: This observational cross-sectional study included a random sample of 94 hospital personnel: 37 general nurse midwives, 47 ophthalmic assistants, and 10 patient caretakers (PCTs). Participants were administered a questionnaire about glaucoma surgery and post-surgery counseling of patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Interestingly, paramedics in close contact with ophthalmologists demonstrated better knowledge than other more educated cadres. [ 4 ] This may be because they are witnesses to regular, correct counseling and often observe firsthand the consequences of poor treatment-seeking behavior. Another study revealed that visits to ophthalmologists are the primary source of glaucoma awareness among health-care workers.…”
mentioning
confidence: 99%
“…Interestingly, paramedics in close contact with ophthalmologists demonstrated better knowledge than other more educated cadres. [ 4 ] This may be because they are witnesses to regular, correct counseling and often observe firsthand the consequences of poor treatment-seeking behavior. Another study revealed that visits to ophthalmologists are the primary source of glaucoma awareness among health-care workers.…”
mentioning
confidence: 99%